Determination of Rare Earth Elements and Thorium at Nanogram Levels in Ultramafic Samples by Inductively Coupled Plasma‐Mass Spectrometry Combined with Chemical Separation and Pre‐concentration. Issue 1 (16th July 2012) - Sun, Yali; Sun, Shengling; Wang, Christina Yan; Xu, Peng
Abstract : A method was developed for the determination of low‐level rare earth elements (REEs) and thorium in ultramafic samples by inductively coupled plasma‐mass spectrometry. The conventional method for the digestion of ultramafic rocks using HNO3 and HF results in considerable amounts of insoluble fluorides because of the high contents of Mg (generally up to 24% m/m) in these rocks. In this study, we used H3 BO3 as a complexing agent to break down the insoluble fluorides, and then separated the REEs from Fe and Mg major and Ba, Ca, Cr minor matrices by anion exchange and co‐precipitation, respectively. The whole procedural blanks estimated from sample‐free analyses ranged from 0.232 ng for Ce to 0.006 ng for Tm and Lu. Limits of detection for this method, defined as three times the standard deviation of these blank analyses, varied from 0.51 ng g −1 for Ce to 0.03 ng g −1 for Lu. The recovery of REEs using this technique, as determined using the standard addition method, ranged from 92.9% for Y to 102.0% for Er with 3% (RSD) variation. The method was validated using GAS (Geo PT ‐12), JP‐1 and PCC‐1, and the results were comparable to literature values, elucidating the applicability to the determination of ultra trace REEs in ultramafic rocks.